Integration of Tri Hita Karana and Sustainable Design for Creative Tourism Villages: Spatial Models in Bongkasa Pertiwi Village - Gede Eri Sumantara; Ngurah Gede Dwi Mahadipta; I Kadek Pranajaya (Universitas Pasundan, 2026)
The village of Bongkasa Pertiwi has significant potential for cultural tourism and the creative economy; however, the area's spatial planning, circulation, facilities, and sanitation are not yet optimal, thereby reducing the quality of the tourist experience and the destination's competitiveness. Furthermore, there is currently no tourism village design model that integrates the Tri Hita Karana philosophy with spatially measurable sustainability indicators. This study aims to formulate a creative tourism area design model based on eco-cultural sustainable design. The method used is design research employing the Glass Box approach, combined with spatial analysis, behavioral mapping, tropical climate analysis, and area utility evaluation. The research results show an increase in circulation efficiency of approximately 30%, the provision of green open spaces covering approximately 40% of the area, a reduction in stormwater runoff of approximately 35%, and an increase in public facility capacity of approximately 25%. This study produces a Tri Hita Karana-based spatial strategy model that supports the development of sustainable, adaptive, and locally-rooted cultural tourism villages. The village of Bongkasa Pertiwi has significant potential for cultural tourism and the creative economy; however, the area's spatial planning, circulation, facilities, and sanitation are not yet optimal, thereby reducing the quality of the tourist experience and the destination's competitiveness. Furthermore, there is currently no tourism village design model that integrates the Tri Hita Karana philosophy with spatially measurable sustainability indicators. This study aims to formulate a creative tourism area design model based on eco-cultural sustainable design. The method used is design research employing the Glass Box approach, combined with spatial analysis, behavioral mapping, tropical climate analysis, and area utility evaluation. The research results show an increase in circulation efficiency of approximately 30%, the provision of green open spaces covering approximately 40% of the area, a reduction in stormwater runoff of approximately 35%, and an increase in public facility capacity of approximately 25%. This study produces a Tri Hita Karana-based spatial strategy model that supports the development of sustainable, adaptive, and locally-rooted cultural tourism villages.